An ultrathin and compact electron transport layer made from novel water-dispersed Fe3O4 nanoparticles to accomplish UV-stable perovskite solar cells. Issue 11 (26th April 2021) - Fang, Song; Chen, Bo; Gu, Bangkai; Meng, Linxing; Lu, Hao; Li, Chang Ming
Abstract : Here we report a UV stable perovskite solar cell with an Fe2 O3 ETL made by spin-coating water dispersed Fe3 O4 nanoparticles. Devices show nearly no decrease of PCE upon continuous exposure to very high UV light irradiation for 10 hours. Abstract : UV induced decomposition of perovskite material is one of the main factors to severely destroy perovskite solar cells for instability. Here we report a UV stable perovskite solar cell with an Fe2 O3 electron transport layer (ETL) made by spin-coating water dispersed Fe3 O4 nanoparticles. Devices with Fe2 O3 ETLs prepared from 10 nm Fe3 O4 nanoparticles show nearly no decrease of photoelectric conversion efficiency (PCE) upon continuous exposure to very high UV light irradiation (300 W Xe lamp) for 10 hours in contrast to the TiO2 ETL based samples with more than 30% reduction of PCE, and their PCE (14.33) is also much superior to those of devices with Fe2 O3 ETLs made conventionally from FeCl3 solution (7.7%). Through the study of Fe2 O3 thin film prepared perovskite solar cells, it is found that compact, high transmittance, low leakage and low transmission impedance devices can be obtained by using an appropriate size of Fe3 O4 nanoparticles. Our major findings are expected to provide a guide to design UV-protected compact electron transport layers for UV-stable perovskite solar cells.